2013
DOI: 10.1038/ijos.2013.67
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of two calcium phosphate pastes on the remineralization of artificial caries: a randomized controlled double-blind in situ study

Abstract: To test the efficacy of two calcium phosphate pastes compared to that of fluoride toothpaste on remineralizing artificial caries in situ, this study had a double-blind crossover in situ design, involving three experimental phases of 14 days each, with an 8-day washout period between phases. Nine healthy subjects participated in the study. The subjects wore removable palatal appliances mounted with six human enamel slabs with artificial caries lesions, and in each of the experimental phases, used one of the fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 15 publications
2
31
1
3
Order By: Relevance
“…By integrating the RBX technology, cross‐polarized‐mode processing of subsurface red and brown features enables visualization of conditions such as rosacea, spider veins, melasma, and acne. Image‐Pro Plus (IPP ® ) is an image analysis software that has been widely used in many fields such as oral science, ophthalmology, pathology, and dermatology . Recently, IPP ® has been introduced into the field of beauty and cosmetics.…”
Section: Discussionmentioning
confidence: 99%
“…By integrating the RBX technology, cross‐polarized‐mode processing of subsurface red and brown features enables visualization of conditions such as rosacea, spider veins, melasma, and acne. Image‐Pro Plus (IPP ® ) is an image analysis software that has been widely used in many fields such as oral science, ophthalmology, pathology, and dermatology . Recently, IPP ® has been introduced into the field of beauty and cosmetics.…”
Section: Discussionmentioning
confidence: 99%
“…In respect of CPP-ACP, Vanichvatana and Auychai [2013] in their in situ study demonstrated that CPP-ACP with F has a remineralising effect on the enamel lesions as well as F, but no additional benefit of CPP-ACP with F associated with fluoride dentifrice was seen compared to fluoride dentifrice only. Another in situ study using CPP-ACP without fluoride showed that this product was less effective than fluoride dentifrice (long-term use) in remineralising caries lesions [Meyer-Lueckel et al, 2015].…”
Section: Discussionmentioning
confidence: 99%
“…To overcome demineralization leading to secondary caries, NACP and nanoparticles of dicalcium phosphate anhydrous (DCPA) have been added into composites. The addition and release of calcium phosphate ions may help remineralize the surrounding dentin to help inhibit secondary caries . These therapeutic composites with calcium and phosphate ions have been shown to effectively remineralize enamel and dentin lesions in vitro .…”
Section: Strategies To Address Challenges Facing Dental Compositesmentioning
confidence: 99%